FRACTURE OF THE CENTRAL TARSAL BONE IN NONRACEHORSES: FOUR CASES. Issue 4 (1st March 2016) - Knuchell, Jeannie A.; Spriet, Mathieu; Galuppo, Larry D.; Katzman, Scott A.
Abstract : Fractures of the central tarsal bone are a rarely recognized cause of acute severe hind limb lameness in nonracehorses. Diagnosis of these fractures can be challenging and little is known about their configuration or outcome. The objectives of this retrospective case series study were to describe the clinical features, imaging findings, and outcomes of fractures of the central tarsal bone in a sample of nonracehorses. Medical records from 2001 to 2014 were searched for cases of central tarsal bone fractures in nonracehorses. All available imaging findings including radiography, ultrasound, computed tomography (CT), and/or nuclear scintigraphy were reviewed. History, clinical presentation, and outcome were collected from the records. Four horses met the inclusion criteria. All had a similar configuration as a simple nondisplaced slab fracture in a dorsomedial to plantarolateral orientation. Initial radiographs failed to reveal the fracture in three of four cases. When additional plantarolateral‐dorsomedial oblique radiographic views were obtained, the fracture could be identified in all cases. Fractures of the central tarsal bone seemed to occur in a consistent dorsomedial to plantarolateral orientation in this sample of nonracehorses, which is different from the configuration previously reported in racehorses. While CT can be used for detection and assessment of these fractures, authors propose that radiography can also identify these fractures with the appropriate view. Authors recommend the use of several plantarolateral to dorsomedial radiographic projections at varying degrees of obliquity for horses with a suspected central tarsal bone fracture.